Mechanized Transplanting Improves Yield and Reduces Pyricularia oryzae Incidence of Paddies in Calasparra Rice of Origin in Spain - María Jesús Pascual-Villalobos; María Martínez; Sergio López; María Pilar Hellín; Nuria López; José Sáez; María del Mar Guerrero; Pedro Guirao (AgriEngineering)
The rice variety Bomba is grown in Calasparra—a rice of origin in southeast Spain—resulting in a product with excellent cooking quality, although its profitability has declined in recent years due to low grain yields and susceptibility to rice blast disease (Pyricularia oryzae Cavara). An innovation project to test the efficacy of mechanized transplanting against traditional direct seed sowing was conducted in 2022 and 2023 at four locations for the first time. A lower plant density (67–82 plants m−2) and shorter plants with higher leaf nitrogen content were observed in transplanted plots compared with seed sowing (130–137 plants m−2) in the first year. The optimal climatic conditions for P. oryzae symptom appearance were determined as temperatures of 25–29 °C and a 50–77% relative humidity. The most-affected sowing plots presented 3–20% leaf area damage and a reduction in yield to values of 1.5 t ha−1 in the first year and 2.12 t ha−1 in the second year. In transplanted plots, there was generally less humidity at the plant level and therefore, disease incidence was low in both seasons. Grain yields did not significantly differ among the treatments studied; however, there were differences in the yield components of panicle density and the number of grains for panicles. Principal component analysis revealed two principal components that explained 81% of the variability. Variables related to yield contributed positively to the first component, while plant biomass variables contributed to the second component. Plant density, tiller density, and panicle density were found to be positively correlated (r > 0.81 ***). Overall, transplanting (frame of 30 × 15–18 cm2) resulted in uniform crop growth with less rice blast disease, as well as higher grain yields (2.92–3.89 t ha−1), in comparison with the average for the whole D.O. Calasparra (2.3–2.5 t ha−1) in both seasons and a good percentage of whole grains at milling. This is novel knowledge which can be considered useful for farmers operating in the region.